PENGEMBANGAN PEGAWAI DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN SUMEDANG - Dian Herlina (JRPA - Journal of Regional Public Administration, 2018)
This study aims to obtain objective data and information regarding employee development, constraints in employee development,and efforts to overcome employee development obstacles in the Sumedang Regency Archive and Library Office. Teh method used is a qualitative research method (naturalistic setting) with descriptive type. The sampling technique used was purvosive sampling with 5 (five) research informants. Data collection techniques through primary data collection techniques such as observation and interviews, secondary data collectin techniques such as library studies and documentation. In analyzing the data used the Hasibuan model’s with the steps: Data education, Data presentation, Conclusion drawing/verification, and Triangulation.Based on the results of the study concluded that the Development of Employees in the Arcive and Library Office of the Sumedang District is still not optimal, because the development method benchmarks on aspects of quality and quantity of employee work are still low, the level of employee discipline is still lacking, effectiviness and efficiency of employee work that is still less, and still not meeting the determined targets. There are efforts to overcome these obstacles by identifying learning objectives, establishing appropriate methods, determining implementation and support